A heavy calcium carbonate composite powder, its preparation method and application

Modifying heavy calcium carbonate by compatible modifiers to form nanoparticles with MOF structure, solving the problems of poor dispersion and lack of antibacterial properties, achieving good dispersion and significant antibacterial effects in the coating, and improving the impact and deodorization properties of the coating.

CN119752218AInactive Publication Date: 2025-04-04HANCHENG YUXING IND CO LTD

Patent Information

Application Number
CN202411967014.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Heavy calcium carbonate is poor in dispersion when used as a filler, easily agglomerate, affects material properties, and lacks antibacterial properties.

Method used

Heavy calcium carbonate is modified by compatible modifiers to form nanoparticles with MOF structure, improve their dispersion, and impart antibacterial properties through the fixation and functionalization of zinc ions.

Benefits of technology

The dispersion of heavy calcium carbonate in the coating is improved, the antibacterial effect is enhanced, and the porous structure of nanoparticles improves the adsorption ability to odor and improves the impact resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005218592870000081
    Figure BDA0005218592870000081
  • Figure BDA0005218592870000091
    Figure BDA0005218592870000091
Patent Text Reader

Abstract

The invention discloses a preparation method of a heavy calcium carbonate composite powder, which belongs to the technical field of composite powders. The method comprises the following steps: a compatible modifier is prepared by Schiff base reaction of aldehyde groups and amino groups of 1,3,6,8-tetrakis(4-formaldehyde phenyl)-pyrene and 2,5-diaminobenzoic acid, and the compatibility modifier can form chemical bonds with calcium ions on the surface of heavy calcium carbonate and wrap the surface; zinc nitrate is dissolved in DMF, and the zinc ions are coordinated with N atoms of 2-methylimidazole to achieve further fixation and functionalization of the zinc ions, thereby having significant antibacterial effects on various bacteria; nanoparticles with an MOF structure are in situ generated on the surface of the modified heavy calcium carbonate, and ammonia and hydrogen sulfide in the air can be adsorbed to reduce odor generated in a laboratory; the prepared heavy calcium carbonate composite powder has a core-shell structure, so that the coating can better disperse and absorb energy when impacted, thereby improving the impact resistance of the coating and extending the service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heavy calcium carbonate functional fillers, and specifically relates to a heavy calcium carbonate composite powder and a preparation method and application thereof. Background Art

[0002] Heavy calcium carbonate (heavy calcium carbonate for short) is an important industrial raw material, mainly composed of calcium carbonate, processed from calcite as raw material, in the form of white powder, and plays an indispensable role in many industrial fields. In the rubber industry, heavy calcium carbonate, as a key filler, can significantly improve the volumetric efficiency of rubber products, thereby effectively reducing dependence on expensive natural rubber and achieving the purpose of reducing costs. In the plastics industry, it can not only improve the dimensional stability and hardness of plastic products, but also improve the gloss and surface smoothness of products. In addition to the rubber and plastics industries, heavy calcium carbonate has also been widely used in many daily chemical industries such as coatings, cables, building supplies and textiles. In these fields, heavy calcium carbonate is mainly used as a filler to reduce costs by increasing the volume of the product, and helps to improve the physical and chemical properties of the product and enhance the overall performance.

[0003] Chinese patent application CN104946039A discloses a metal roof thermal insulation and waterproof coating and a preparation method thereof. The additives other than the thickener are dissolved in part of the water, and zinc oxide, nano titanium dioxide and heavy calcium carbonate are added and stirred evenly. This not only gives the coating good low-temperature flexibility, waterproof performance and thermal insulation effect, but also has excellent mechanical properties. However, this physical doping method causes the filler to be unevenly distributed in the matrix, forming agglomerations, which in turn affects the performance of the material. Summary of the invention

[0004] The purpose of the present invention is to solve the problem of poor dispersibility and easy agglomeration of heavy calcium carbonate when used as a filler by modifying heavy calcium carbonate to form a heavy calcium carbonate composite powder, and on this basis, to give the heavy calcium carbonate composite powder antibacterial properties.

[0005] A method for preparing a heavy calcium carbonate composite powder comprises the following steps:

[0006] Step 1: Add 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, 2,5-diaminobenzoic acid and deionized water into a reactor, stir at a speed of 500-700r / min for 30-50min, then gradually add o-dichlorobenzene, n-butanol and acetic acid solution with a molar concentration of 6mol / L into the reactor, ultrasonically disperse for 40-60min, continue to stir and react at 20-25°C for 1-2h, then degas through 3-5 liquid nitrogen freeze-vacuum-thaw cycles, heat to 115-125°C under vacuum conditions for 70-80h, filter, wash the filter cake with tetrahydrofuran 2-3 times, and vacuum dry at 60-80°C for 1-2h to obtain a compatible modifier.

[0007] Step 2: Add the compatible modifier and 20-30% DMSO aqueous solution into the reactor, stir at 500-700r / min for 20-30min, add heavy calcium carbonate base powder, stir and react at 15-20°C for 1.5-2h, ultrasonically disperse for 40-60min, filter, wash the filter cake with deionized water for 3-5 times, and vacuum dry at 60-80°C for 1-2h to obtain modified heavy calcium carbonate powder.

[0008] Step 3: Evenly mix the modified heavy calcium carbonate powder, zinc nitrate hexahydrate and DMF, and ultrasonically disperse for 40-60 minutes to obtain a mixed dispersion of heavy calcium carbonate; add 2-methylimidazole, DMF and deionized water into a reactor, ultrasonically disperse for 40-60 minutes, and stir at a speed of 500-700 r / min for 30-50 minutes to obtain an organic ligand solution; add the heavy calcium carbonate dispersion into a reactor containing the organic ligand solution, ultrasonically disperse for 40-60 minutes, stir the reaction at 150-170°C and 500-700 r / min for 10-12 hours, cool naturally, centrifuge and wash with distilled water and anhydrous ethanol for 2-3 times, and vacuum dry at 60-80°C for 1-2 hours to obtain a composite powder of heavy calcium carbonate.

[0009] Furthermore, the heavy calcium carbonate-based powder in step 2 is prepared by the following steps:

[0010] The calcite is crushed into a diameter of 2-3 mm by a crusher to obtain a coarse calcium carbonate material. The coarse calcium carbonate material, deionized water and polyvinyl alcohol as a dispersant are mixed evenly and then foamed for 20-30 minutes. Then, the mixture is transferred to a ball mill and wet-milled at a speed of 300-400 r / min for 10-15 minutes. The obtained slurry is spray-dried at 150-200° C. to obtain a heavy calcium carbonate-based powder with a diameter of 5-10 μm.

[0011] Furthermore, the usage ratio of the calcium carbonate coarse material, deionized water and the dispersant polyvinyl alcohol is 60-80 g: 120-180 mL: 2.8-3.2 g.

[0012] Furthermore, in step one, the dosage ratio of 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, 2,5-diaminobenzoic acid, deionized water, o-dichlorobenzene, n-butanol, acetic acid solution and tetrahydrofuran is 40-50 g: 20-30 g: 120-180 mL: 5-5.5 mL: 5-5.5 mL: 1-1.5 mL: 8-9 mL.

[0013] Furthermore, in step 2, the usage ratio of the compatible modifier, the DMSO aqueous solution and the heavy calcium carbonate-based powder is 40-50 g: 70-75 mL: 50-70 g.

[0014] Furthermore, in step three, the dosage ratio of the heavy calcium carbonate mixed dispersion and the organic ligand solution is 4-5 mL: 64-82 mL.

[0015] Furthermore, in the step 3, the dosage ratio of the modified heavy calcium carbonate powder, zinc nitrate hexahydrate and DMF in the heavy calcium carbonate mixed dispersion is 50-60 g: 3.8-4.4 g: 40-45 mL.

[0016] Furthermore, in step 3, the dosage ratio of 2-methylimidazole, DMF and deionized water in the organic ligand solution is 3.8-4.5 g: 40-45 mL: 60-80 mL.

[0017] The invention also provides an application of the heavy calcium carbonate composite powder as a functional filler in coatings.

[0018] Beneficial effects of the present invention:

[0019] 1. The heavy calcium carbonate composite powder prepared by the present invention is modified by a compatible modifier, which helps to improve its dispersibility in the coating. The compatible modifier is 1,3,6,8-tetrakis (4-formaldehyde phenyl) -pyrene, 2,5-diaminobenzoic acid, which undergoes a Schiff base reaction through an aldehyde group and an amino group to generate a covalent organic framework. The compatible modifier contains a large number of carboxyl groups, which can form chemical bonds with calcium ions on the surface of the heavy calcium carbonate, which helps the compatible modifier to be wrapped on the surface of the heavy calcium carbonate. The porous structure of the compatible modifier can produce a steric hindrance effect, which can prevent direct contact and agglomeration between heavy calcium carbonate particles, thereby improving its dispersibility in the matrix and enhancing its use effect as a filler in the coating.

[0020] 2. In the composite dispersion of heavy calcium carbonate of the present invention, zinc nitrate is dissolved in DMF, zinc ions are fully released and dispersed in DMF, and these zinc ions are adsorbed on the surface of modified heavy calcium carbonate. The surface properties of the heavy calcium carbonate particles are changed after modification, thereby enhancing their adsorption capacity for zinc ions. Then, the heavy calcium carbonate particles are added to the organic ligand solution, and the zinc ions react with the N atoms of 2-methylimidazole to achieve further fixation and functionalization of the zinc ions on the surface of the modified heavy calcium carbonate, and nanoparticles with a MOF structure are in situ generated on the surface of the modified heavy calcium carbonate, which have significant antibacterial effects on a variety of bacteria, and the antibacterial effect is long-lasting.

[0021] 3. The heavy calcium carbonate composite powder prepared by the present invention can be used in coatings, and not only has a good antibacterial effect, but also can adsorb ammonia and hydrogen sulfide in the air, reducing the odor generated in the laboratory. The adsorption capacity of the nanoparticles on the surface of the modified heavy calcium carbonate particles mainly comes from the amino and carboxylic acids in their structure, which can form hydrogen bonding forces with ammonia and hydrogen sulfide, and the nanoparticles have a porous structure, which helps to improve the adsorption capacity of odor molecules.

[0022] 4. The present invention wraps the compatible modifier on the surface of heavy calcium carbonate and generates nanoparticles with MOF structure in situ on the surface. The prepared heavy calcium carbonate composite powder has a core-shell structure. The core layer and the shell layer can slide relative to each other, which helps to disperse stress. When the paint coating is impacted, it can better disperse and absorb energy, thereby improving the impact resistance of the coating and helping to extend the service life. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Embodiment 1: A method for preparing a heavy calcium carbonate composite powder, comprising the following steps:

[0025] S1: The calcite was crushed into a diameter of 2 mm by a pulverizer to obtain a coarse calcium carbonate material. 6 kg of the coarse calcium carbonate material, 12 L of deionized water and 280 g of polyvinyl alcohol as a dispersant were mixed evenly and then slurried for 20 min. The mixture was then transferred to a ball mill and wet-milled at a speed of 300 r / min for 10 min. The obtained slurry was spray-dried at 150° C. to obtain a heavy calcium carbonate-based powder with a diameter of 5 μm.

[0026] S2: 4 kg of 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, 2 kg of 2,5-diaminobenzoic acid and 12 L of deionized water were added to a reactor, stirred at a speed of 500 r / min for 30 min, and then 500 mL of o-dichlorobenzene, 500 mL of n-butanol and 100 mL of 6 mol / L acetic acid solution were gradually added dropwise to the reactor, ultrasonically dispersed for 40 min, stirred and reacted at 20°C for 1 h, and then degassed through 3 liquid nitrogen freeze-vacuum-thaw cycles, heated to 115°C under vacuum conditions for 70 h, filtered, washed the filter cake twice with 800 mL of tetrahydrofuran, and dried in vacuo at 60°C for 1 h to obtain a compatible modifier.

[0027] S3: Add 4 kg of compatible modifier and 7 L of 20% DMSO aqueous solution into the reactor, stir at 500 r / min for 20 min, add 5 kg of heavy calcium carbonate base powder, stir and react at 15 ° C for 1.5 h, ultrasonically disperse for 40 min, filter, wash the filter cake with deionized water 3 times, and vacuum dry at 60 ° C for 1 h to obtain modified heavy calcium carbonate powder.

[0028] S4: 5 kg of modified heavy calcium carbonate powder, 380 g of zinc nitrate hexahydrate and 4 L of DMF were mixed evenly, and ultrasonically dispersed for 40 min to obtain a mixed dispersion of heavy calcium carbonate; 380 g of 2-methylimidazole, 4 L of DMF and 6 L of deionized water were added to a reactor, ultrasonically dispersed for 40 min, and stirred at a speed of 500 r / min for 30 min to obtain an organic ligand solution; the heavy calcium carbonate dispersion was added to a reactor containing the organic ligand solution, ultrasonically dispersed for 40 min, stirred for reaction at 150° C. and 500 r / min for 10 h, cooled naturally, centrifuged and washed twice with distilled water and anhydrous ethanol respectively, and vacuum dried at 60° C. for 1 h to obtain a heavy calcium carbonate composite powder.

[0029] Embodiment 2: A method for preparing a heavy calcium carbonate composite powder, comprising the following steps:

[0030] S1: The calcite was crushed into a diameter of 2.5 mm by a pulverizer to obtain a coarse calcium carbonate material. 7 kg of the coarse calcium carbonate material, 15 L of deionized water and 300 g of polyvinyl alcohol as a dispersant were mixed evenly and then slurried for 25 minutes. The mixture was then transferred to a ball mill and wet-milled at a speed of 350 r / min for 13 minutes. The obtained slurry was spray-dried at 180° C. to obtain a heavy calcium carbonate-based powder with a diameter of 7 μm.

[0031] S2: 4.5 kg of 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, 2.5 kg of 2,5-diaminobenzoic acid and 15 L of deionized water were added to a reactor, stirred at 600 r / min for 40 min, and then 520 mL of o-dichlorobenzene, 520 mL of n-butanol and 120 mL of 6 mol / L acetic acid solution were gradually added dropwise to the reactor, ultrasonically dispersed for 50 min, and stirred for reaction at 22 ° C for 1.5 h, and then degassed through 4 liquid nitrogen freeze-vacuum-thaw cycles, heated to 120 ° C under vacuum conditions for reaction for 75 h, filtered, and the filter cake was washed 3 times with 850 mL of tetrahydrofuran, and vacuum dried at 70 ° C for 1.5 h to obtain a compatible modifier.

[0032] S3: Add 4.5 kg of compatible modifier and 7.2 L of 25% DMSO aqueous solution into the reactor, stir at 600 r / min for 25 min, add 6 kg of heavy calcium carbonate base powder, stir and react at 18°C ​​for 1.5 h, ultrasonically disperse for 50 min, filter, wash the filter cake with deionized water 4 times, and vacuum dry at 70°C for 1.5 h to obtain modified heavy calcium carbonate powder.

[0033] S4: 6 kg of modified heavy calcium carbonate powder, 400 g of zinc nitrate hexahydrate and 4.3 L of DMF were mixed evenly, and ultrasonically dispersed for 50 min to obtain a heavy calcium carbonate mixed dispersion; 400 g of 2-methylimidazole, 4.3 L of DMF and 7 L of deionized water were added to a reactor, ultrasonically dispersed for 50 min, and stirred at a speed of 600 r / min for 40 min to obtain an organic ligand solution; the heavy calcium carbonate dispersion was added to a reactor containing the organic ligand solution, ultrasonically dispersed for 50 min, stirred for reaction at 160° C. and 600 r / min for 11 h, cooled naturally, centrifuged and washed with distilled water and anhydrous ethanol for 3 times respectively, and vacuum dried at 70° C. for 1.8 h to obtain a heavy calcium carbonate composite powder.

[0034] Embodiment 3: A method for preparing a heavy calcium carbonate composite powder, comprising the following steps:

[0035] S1: The calcite was crushed into a diameter of 3 mm by a pulverizer to obtain a coarse calcium carbonate material. 8 kg of the coarse calcium carbonate material, 18 L of deionized water and 320 g of polyvinyl alcohol as a dispersant were mixed evenly and then slurried for 30 minutes. The mixture was then transferred to a ball mill and wet-milled at a speed of 400 r / min for 15 minutes. The obtained slurry was spray-dried at 200°C to obtain a heavy calcium carbonate-based powder with a diameter of 10 μm.

[0036] S2: Add 5kg of 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, 3kg of 2,5-diaminobenzoic acid and 18L of deionized water into a reactor, stir at 700r / min for 50min, then gradually add 550mL of o-dichlorobenzene, 550mL of n-butanol and 150mL of 6mol / L acetic acid solution into the reactor, ultrasonically disperse for 60min, continue stirring and reacting at 25°C for 2h, then degas through 5 cycles of liquid nitrogen freezing-vacuuming-thawing program, heat to 125°C under vacuum conditions for 80h, filter, wash the filter cake with 900mL of tetrahydrofuran 3 times, and vacuum dry at 80°C for 2h to obtain a compatible modifier.

[0037] S3: Add 5 kg of compatible modifier and 7.5 L of 30% DMSO aqueous solution into the reactor, stir at 700 r / min for 30 min, add 7 kg of heavy calcium carbonate base powder, stir and react at 20°C for 2 h, ultrasonically disperse for 60 min, filter, wash the filter cake with deionized water 5 times, and vacuum dry at 80°C for 2 h to obtain modified heavy calcium carbonate powder.

[0038] S4: 7 kg of modified heavy calcium carbonate powder, 440 g of zinc nitrate hexahydrate and 4.5 L of DMF were mixed evenly, and ultrasonically dispersed for 60 min to obtain a mixed dispersion of heavy calcium carbonate; 450 g of 2-methylimidazole, 4.5 L of DMF and 8 L of deionized water were added to a reactor, ultrasonically dispersed for 60 min, and stirred at 700 r / min for 50 min to obtain an organic ligand solution; the heavy calcium carbonate dispersion was added to a reactor containing the organic ligand solution, ultrasonically dispersed for 60 min, stirred for reaction at 170°C and 700 r / min for 12 h, cooled naturally, centrifuged and washed 3 times with distilled water and anhydrous ethanol respectively, and vacuum dried at 80°C for 2 h to obtain a heavy calcium carbonate composite powder.

[0039] Comparative Example 1: Heavy calcium carbonate-based powder prepared by the method of step S1 in Example 3.

[0040] Comparative Example 2: Modified heavy calcium carbonate powder prepared by the method of steps S1-S3 in Example 3.

[0041] Comparative Example 3: Based on Example 3, in step S4, the modified heavy calcium carbonate powder in step S3 is directly replaced by the heavy calcium carbonate base powder prepared by the method of step S1, and the other steps remain unchanged to prepare a heavy calcium carbonate composite powder.

[0042] The dispersants in Examples 1 to 3 were polyvinyl alcohol, all of which were purchased from Shanghai Ruichu Biotechnology Co., Ltd.

[0043] Application example: Heavy calcium carbonate composite powder can be used as a functional filler in coatings, including but not limited to water-based epoxy resin coatings.

[0044] Performance tests were performed on Examples 1 to 3 and Comparative Examples 1 to 3, taking the waterborne epoxy resin coating prepared by the following method as an example:

[0045] The heavy calcium carbonate composite powder in Examples 1 to 3 and Comparative Example 3, the heavy calcium carbonate base powder in Comparative Example 1, and the modified heavy calcium carbonate powder in Comparative Example 2 are respectively used as functional fillers, and then water-based epoxy resin, functional filler, curing agent, defoaming agent, leveling agent, dispersant and deionized water are uniformly stirred in a mass ratio of 50:30:2:2:0.5:1.5:11 to obtain different water-based epoxy resin coatings.

[0046] The above-mentioned curing agent is diethylenetriamine purchased from Shanghai Kain Chemical Co., Ltd.; the defoaming agent is polyether modified polysiloxane purchased from Foshan Nanhai Datian Chemical Co., Ltd.; the leveling agent is acrylic epoxy ink purchased from Foshan Qianyou Chemical Co., Ltd.; the dispersing agent is sodium polyacrylate PAAS purchased from Jinan Delan Chemical Co., Ltd.

[0047] Apply different water-based epoxy resin coatings on the metal substrate, and after curing, obtain samples with the same coating thickness. Refer to GB / T1732-2020 to test the impact resistance of the coatings of different samples;

[0048] According to GB / T21866-2008, Staphylococcus aureus (ATCC25923) was quantitatively inoculated on different samples, and the antibacterial rate of the coating of different samples was tested and calculated by the film sticking method (R = (BC) / B×100%);

[0049] B: Average number of recovered bacteria in the blank control plate after 24 hours (cfu / plate);

[0050] C: Average number of recovered bacteria on the antimicrobial coating sample after 24 hours (cfu / piece);

[0051] Five closed containers made of transparent acrylic plates with a size of 1m×1m×1m were prepared, and samples with different sizes of 10cm×10cm×10cm were placed in the closed containers. Odor was introduced into the closed containers, and the hydrogen sulfide content in the odor was controlled to be 30ppm and the ammonia concentration to be 70ppm in the initial state. After standing for 30 minutes, the concentrations of hydrogen sulfide and ammonia in the closed containers were tested again to evaluate the deodorizing performance of samples with different coatings.

[0052] The results are shown in Table 1:

[0053] Table 1

[0054]

[0055]

[0056] As can be seen from Table 1, the impact resistance of the coating formed by using the heavy calcium carbonate composite powder in Examples 1 to 3 as a functional filler is significantly better than that of the comparative example. The compatibility modifier forms a chemical bond with the calcium ions on the surface of the heavy calcium carbonate and is wrapped on the surface of the heavy calcium carbonate. Its porous structure can produce a steric hindrance effect, which can prevent direct contact and agglomeration between the heavy calcium carbonate particles, improve the dispersibility in the matrix, and make the coating more evenly dispersed. When impacted, it can better absorb energy, thereby improving the impact resistance of the coating; the antibacterial performance of Examples 1 to 3 is significantly better than that of the comparative example. By forming nanoparticles with a MOF structure, further fixation and functionalization of zinc ions on the surface of the modified heavy calcium carbonate are achieved, which can significantly increase the antibacterial effect of the coating; the gas absorption ability of Examples 1 to 3 is significantly better than that of the comparative example. The formed nanoparticles can form hydrogen bonding forces with ammonia and hydrogen sulfide, and the nanoparticles have a porous structure, which helps to improve the adsorption capacity of ammonia and hydrogen sulfide.

[0057] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0058] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a heavy calcium carbonate composite powder, characterized in that: The following steps are involved: Step 1: Add 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, 2,5-diaminobenzoic acid and deionized water into a reaction kettle, stir at 500-700r / min for 30-50min, then drop o-dichlorobenzene, n-butanol and 6mol / L acetic acid solution, ultrasonically disperse for 40-60min, stir at 20-25°C for 1-2h, then degas through 3-5 cycles of liquid nitrogen freezing-vacuuming-thawing, heat to 115-125°C under vacuum conditions for 70-80h, filter, wash the filter cake with tetrahydrofuran 2-3 times, and vacuum dry to obtain a compatible modifier; Step 2: Add the compatible modifier and 20-30wt% DMSO aqueous solution into the reactor, stir at 500-700r / min for 20-30min, then add the heavy calcium carbonate base powder, stir and react at 15-20°C for 1.5-2h, ultrasonically disperse for 40-60min, filter, wash the filter cake, and vacuum dry to obtain modified heavy calcium carbonate powder; Step 3: Evenly mix the modified heavy calcium carbonate powder, zinc nitrate hexahydrate and DMF, and ultrasonically disperse for 40-60 minutes to obtain a mixed dispersion of heavy calcium carbonate; add 2-methylimidazole, DMF and deionized water into a reactor, ultrasonically disperse for 40-60 minutes, and stir at 500-700 r / min for 30-50 minutes to obtain an organic ligand solution; add the heavy calcium carbonate dispersion into a reactor containing the organic ligand solution, ultrasonically disperse for 40-60 minutes, stir at 150-170°C and 500-700 r / min for 10-12 hours, cool naturally, centrifuge and wash with distilled water and anhydrous ethanol for 2-3 times, and vacuum dry to obtain a composite powder of heavy calcium carbonate.

2. The method for preparing a heavy calcium carbonate composite powder according to claim 1, characterized in that: In step 1, the dosage ratio of 1,3,6,8-tetrakis(4-formaldehydephenyl)-pyrene, 2,5-diaminobenzoic acid, deionized water, o-dichlorobenzene, n-butanol, acetic acid solution and tetrahydrofuran is 40-50 g: 20-30 g: 120-180 mL: 5-10 mL: 5-10 mL: 1-1.5 mL: 80-90 mL.

3. The method for preparing a heavy calcium carbonate composite powder according to claim 1, characterized in that: In step 2, the usage ratio of the compatible modifier, the DMSO aqueous solution and the heavy calcium carbonate-based powder is 40-50 g: 70-75 mL: 50-70 g.

4. The method for preparing a heavy calcium carbonate composite powder according to claim 1, characterized in that: The heavy calcium carbonate-based powder described in step 2 is prepared by the following steps: The calcite is crushed into a diameter of 2-3 mm by a pulverizer, and the obtained calcium carbonate crude material is evenly mixed with deionized water and polyvinyl alcohol, and the slurry is soaked for 20-30 minutes, and then transferred to a ball mill, and wet-milled at 300-400r / min for 10-15 minutes. The obtained slurry is spray-dried at 150-200°C to obtain a heavy calcium carbonate-based powder with a diameter of 5-10μm.

5. The method for preparing a heavy calcium carbonate composite powder according to claim 4, characterized in that: The usage ratio of the calcium carbonate coarse material, deionized water and polyvinyl alcohol is 60-80 g: 120-180 mL: 2.8-3.2 g.

6. The method for preparing a heavy calcium carbonate composite powder according to claim 1, characterized in that: The dosage ratio of the heavy calcium carbonate mixed dispersion liquid and the organic ligand solution is 4-5 mL:64-82 mL.

7. The method for preparing a heavy calcium carbonate composite powder according to claim 1, characterized in that: The dosage ratio of the modified heavy calcium carbonate powder, zinc nitrate hexahydrate and DMF in the heavy calcium carbonate mixed dispersion in step 3 is 50-60 g: 3.8-4.4 g: 40-45 mL.

8. The method for preparing a heavy calcium carbonate composite powder according to claim 1, characterized in that: The dosage ratio of 2-methylimidazole, DMF and deionized water in the organic ligand solution in step 3 is 3.8-4.5 g: 40-45 mL: 60-80 mL.

9. A heavy calcium carbonate composite powder, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 8.

10. Use of the heavy calcium carbonate composite powder according to claim 9 as a functional filler in coatings.

Citation Information

Patent Citations

  • Large-scale adsorbing material ZIF-8 preparation method and forming method

    CN103230777A

  • Metal roof heat-insulating waterproof coating and preparation method thereof

    CN104946039A

  • Antibacterial ozone-resistant modified calcium carbonate and preparation method thereof

    CN104987754A

  • Wear-resistant epoxy resin coating

    CN107974168A

  • Environmentally friendly super-hydrophobic shock-resistant water-borne epoxy resin coating and preparation method thereof

    CN108504256A

Cited By

  • COF (at) MOF composite material and preparation method and application thereof

    CN121005908A